PENGARUH MEDIA PEMBELAJARAN BERBASIS ONLINE PADA MATA PELAJARAN IPS DI SMA NEGERI 2 TONDANO - Mesra, Romi; Marleni, Marleni; Wenno, Yulian Hermanus; Haumahu, Cynthia Petra (Lembaga Penelitian dan Pendidikan Mandala, 2022)
It takes an innovation created by a teacher in order to get maximum learning outcomes because the teacher certainly knows better what the students need because it is the teacher who interacts the most with students in the teaching and learning process at school. Media and learning tools applied by teachers in schools will certainly affect student learning outcomes. The purpose of this study is to reveal the effect of online-based learning media on social studies subjects at SMA Negeri 2 Tondano. The method used is a qualitative research method. The results of this study are; Positive influence of online-based learning media on social studies subjects: Increased competence of teachers and students in using social media for social studies learning, Teachers are more flexible in elaborating social studies teaching materials by providing real examples that are viral on social media, Opening new job opportunities for students, Students more motivated to learn social studies subjects through various social media, students are easier to understand social studies material because it often appears on social media that students play. The negative influence of online-based learning media on social studies subjects; Teachers are